The Samsung way : transformational management strategies from the world leader in innovation and design - Song, Chae-yong, 1964-; Yi, Kyŏng-muk (McGraw Hill-Ascent Audio, 2014)
Learn how to manage, lead, and succeed ... the Samsung way. Based on ten years of research and interviews with 80 top executives, the award-winning The Samsung Way is the first definitive guide to the groundbreaking management principles that transformed a lagging electronics company into one of the most successful brands in the world. Combining professional insights from Samsung insiders with practical applications for managers, executives, and CEOs, this powerhouse of a book shows you how to: Speed up decision making and execution, on a bigger scale. Create a convergence synergy among diversified businesses, while staying competitive in core businesses. Mix and match Western and Eastern management styles. Also known as "The Three Paradoxes of Samsung Management," these seemingly contradictory goals are the keys behind Chairman Lee Kun-Hee's now-famous New Management Initiative-the business plan that drove Samsung to become the number-one leader in mobile phones, televisions, semiconductors, and other electronics. A revolutionary-and time-tested-approach to innovation, Samsung's management principles will help you find the perfect balance of styles by combining the best of all worlds. This ingenious step-by-step guide shows you how to implement Samsung's proven techniques for grafting American business practices onto a Japanese system, thus keeping costs low and bringing about differentiation. You'll learn how to achieve both economies of scale and speed in this era of a hypercompetitive world. Best of all, you'll drive new ideas and innovations at every level of your company while building on your greatest strengths and successes. That's The Samsung Way